2013
DOI: 10.1186/2040-2392-4-51
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling in engrailed-2 mutant mice reveals common molecular pathways associated with autism spectrum disorders

Abstract: BackgroundTranscriptome analysis has been used in autism spectrum disorder (ASD) to unravel common pathogenic pathways based on the assumption that distinct rare genetic variants or epigenetic modifications affect common biological pathways. To unravel recurrent ASD-related neuropathological mechanisms, we took advantage of the En2 -/- mouse model and performed transcriptome profiling on cerebellar and hippocampal adult tissues.MethodsCerebellar and hippocampal tissue samples from three En2 -/- and wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
(91 reference statements)
3
23
1
Order By: Relevance
“…More interestingly, transcriptome analysis of embryonic (E12.5) telencephalon from ARX mutant mice revealed, among deregulated genes, a significant enrichment (12%) of genes implicated in ASD and epilepsy (Mattiske et al ., ). Similarly, we recently showed significant enrichment of ASD and epilepsy genes among differentially expressed genes in the adult hippocampus of En2 knockout ( En2 −/− ) mice (Sgadò et al ., ; Provenzano et al ., ). Moreover, genes involved in pre‐ and postsynaptic GABAergic transmission were significantly enriched among downregulated genes in the En2 −/− adult hippocampus (Provenzano et al ., ).…”
Section: Gabaergic Dysfunction In Asd and Epilepsy: Mouse Model Datamentioning
confidence: 98%
“…More interestingly, transcriptome analysis of embryonic (E12.5) telencephalon from ARX mutant mice revealed, among deregulated genes, a significant enrichment (12%) of genes implicated in ASD and epilepsy (Mattiske et al ., ). Similarly, we recently showed significant enrichment of ASD and epilepsy genes among differentially expressed genes in the adult hippocampus of En2 knockout ( En2 −/− ) mice (Sgadò et al ., ; Provenzano et al ., ). Moreover, genes involved in pre‐ and postsynaptic GABAergic transmission were significantly enriched among downregulated genes in the En2 −/− adult hippocampus (Provenzano et al ., ).…”
Section: Gabaergic Dysfunction In Asd and Epilepsy: Mouse Model Datamentioning
confidence: 98%
“…Other models include the repetitive behavior observed in C58/J, C57BL/6J, and Grin1 knockdown mice (360). The homeobox-containing transcription factor engrailed-2 (En2) is involved in patterning and neuronal differentiation; Sgadò et al (361, 362) showed that adult En2 −/− mice exhibit reduced brain interneuron expression of GABAergic marker mRNAs, and reduction in parvalbumin, somatostatin, and neuropeptide Y in the cerebellum and cerebral cortex (including hippocampus). The genetically inbred BTBR T + Itpr3 tf/J mouse model of ASD exhibits social impairment and stereotypic behavior suggestive of mTOR overactivation (363).…”
Section: Asd and Thyroid Hormones During Brain Developmentmentioning
confidence: 99%
“…Human Engrailed-2 (En2) gene is localized to 7q36, an autism susceptibility locus. This genes were introduced on mouse since 2005[10, [16][17][18][19][20]. However, it is also found in human brain study [21].…”
Section: Engrailed-2mentioning
confidence: 99%